[Afisz. Incipit] Czesław Niemien po sukcesach w Paryżu ... i Niebiesko-Czarni. (Gdańsk : [wydawca nieznany], 1966)
Sztrajfa reklamująca występy artystów.
Keywords: Niemen, Czesław -- (1939-2004) -- druki ulotne; Niebiesko-Czarni -- druki ulotne; Afisze -- 1945-1990.